End‐stage renal disease from hemolytic uremic syndrome in the United States, 1995–2010. Issue 4 (17th February 2015) - Sexton, Donal J.; Reule, Scott; Solid, Craig A.; Chen, Shu‐Cheng; Collins, Allan J.; Foley, Robert N.
Abstract Management of hemolytic uremic syndrome (HUS) has evolved rapidly, and optimal treatment strategies are controversial. However, it is unknown whether the burden of end‐stage renal disease (ESRD) from HUS has changed, and outcomes on dialysis in the United States are not well described. We retrospectively examined data for patients initiating maintenance renal replacement therapy (RRT) (n = 1, 557, 117), 1995–2010, to define standardized incidence ratios (SIRs) and outcomes of ESRD from HUS) (n = 2241). Overall ESRD rates from HUS in 2001–2002 were 0.5 cases/million per year and were higher for patients characterized by age 40–64 years (0.6), ≥65 years (0.7), female sex (0.6), and non‐Hispanic African American race (0.7). Standardized incidence ratios remained unchanged (P ≥ 0.05) between 2001–2002 and 2009–2010 in the overall population. Compared with patients with ESRD from other causes, patients with HUS were more likely to be younger, female, white, and non‐Hispanic. Over 5.4 years of follow‐up, HUS patients differed from matched controls with ESRD from other causes by lower rates of death (8.3 per 100 person‐years in cases vs. 10.4 in controls, P < 0.001), listing for renal transplant (7.6 vs. 8.6 per 100 person‐years, P = 0.04), and undergoing transplant (6.9 vs. 9 per 100 person‐years, P < 0.001). The incidence of ESRD from HUS appears not to have risen substantially in the last decade. However, given that HUS subtypes could not be determined in this study, these findings should be interpreted with caution.